Screen-Space Virtual Point Light propagation for Real-Time Global Illumination - Aranha, Vitor M.; Macedo, Márcio C. F.; Apolinário Jr., Antônio L. (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI), 2021)
Proper light-transport simulation adds both realism and aesthetically pleasing effects to virtual 3D scenes. However, the cost of computing complex light interactions is prohibitive for real-time applications. Indirect diffuse lighting is a low frequency component of global illumination that can greatly enhance the quality of an image. Virtual point lights are commonly used to reproduce diffuse bounces by tracing light paths through the scene and creating proxy light sources at the intersections between a path and geometry. In this work we extend clusterization-based methods for virtual point lights, allowing for the reproduction of up to two bounces of light with a projection-aware sampling method in real-time. We show that plausible images can be obtained in real-time rates for low to mid-end commodity GPUs.